Implementation of Dynamic Lighting & Augmented Reality (DLAR) Smart Home System for Deaf and Hard-of-Hearing (DHH) Residents - Abhirup Bose, M. Safa, Sanjay Bhargav Siddi , Manas Raj Anand, Vivek Kumar (International Journal of Advanced Science and Technology, 2020)
A reliable, secure and two-pronged approach to incorporate IOT smart home principles on top of existing systems to make it a viable solution for deaf & hard-of-hearing (DHH) residents is being proposed. The dynamic lighting & augmented reality(DLAR) System will alert the residents to a sound trigger or a change of state in various smart appliances with a dynamic change of color of all the smart LED lights in the residents personal environment to a predetermined color coded light. The System, installed with a powerful embedded wireless communication module will also send a wireless command to the residents personal device like a mobile phone with an integrated app installed, which will generate a perceptible vibration along with a text pop-up. The app, using AR Technology will point to the direction of the sound, enabling the resident’s to virtually “see” sound. This System is highly accessible and can be easily commercialized as there are no complex electronics requirements and all necessary components can be found and conFigd on an existing typical Smart Home System to incorporate the DLAR principles.Keywords: Deaf, Smart Home System, IoT, Augmented Reality, Sound Triangulation.